Bargaining Coalitions in the Agricultural Negotiations of the Doha Round: Similarity of Interests or Strategic Choices? An Empirical Assessment - Fabrizio De Filippis; Valeria Costantini; Riccardo Crescenzi; Luca Salvatici (Fondazione Eni Enrico Mattei (FEEM), 2005)
The paper aims at understanding the structural features of the bargaining coalitions in the Doha Round of the WTO. We provide an empirical assessment of the preferences of each negotiating actor looking at general economics indicators, development levels, structure of the agricultural sectors, and trade policies for agricultural products. Bargaining coalitions are analyzed by grouping countries through a cluster analysis procedure. The clusters are compared with existing coalitions, in order to assess their degree of internal homogeneity as well as their common interests. Such a comparison allows the detection of possible defectors, i.e. countries that according to their economic conditions and policies seem to be relatively less committed to the positions of the coalition they join.
Keywords: F13; Q17; 330; Agricultural trade negotiations; Bargaining coalitions; WTO; Cluster analysis; Internationale Handelspolitik; Agraraußenhandel; Verhandlungen; Clusteranalyse; Welt